Two-year single centre results with covered endovascular reconstruction of aortic bifurcation (CERAB) in the treatment of extensive aorto-iliac occlusive disease. (June 2022) - Borghese, Ottavia; Ferrer, Ciro; Coscarella, Carlo; Spataro, Claudio; Diotallevi, Nicolò; Giudice, Rocco
Objective: To report the results of a single-centre in the treatment of extensive aorto-iliac occlusive disease (AIOD) by the covered endovascular reconstruction of aortic bifurcation (CERAB) technique. Methods: A retrospective analysis was conducted on data obtained from the review of medical charts of all consecutive patients treated with CERAB technique for AIOD between January 2016 and December 2019 in San Giovanni-Addolorata Hospital (Rome, Italy). Clinical examination, duplex ultrasound with ankle-brachial index measurement and contrast-enhanced computed tomography angiography were performed preoperatively. A clinical and ultrasound follow-up was carried out at one month and then half yearly after the intervention to evaluate patients' clinical status, limb salvage, target lesion revascularization rate, primary and secondary patency rate. Results: During the study period, 24 patients (14 men, 58.3%; 10 women, 41.7%; median age 59 years, range 37–79 years) underwent CERAB for AIOD (TASC II C 29.2%, TASC II D 70.8%). Indications for treatment were: intermittent claudication in 18 patients (75%) and critical limb ischemia in 6 (25%). Technical success was achieved in all cases. Perioperative minor complications occurred in three cases (12.5%). One patient reported an intraoperative iliac rupture requiring adjunctive covered stenting. Median hospital length of stay was two days (range 1–9). No patient died perioperatively nor at the last follow-up. At a median follow-up of 18 months (range 6–48 months), mean ankle-brachial index increased significantly (from 0.62 ± 0.15 before the procedure to 0.84 ± 0.18) ( P  < 0.001) and target lesion revascularization rate was 12.5%. At two years, the limb salvage rate was 100%, and primary and secondary patency rates were 87.5% and 100%, respectively. Conclusion: CERAB technique demonstrated to be effective at the mid-term follow-up with low rate of complications and short length of stay. Long-term results and more robust data are needed to affirm this technique as the first-line treatment for extensive AIOD. However, it could become the preferred option especially in fragile patients and during contemporary COVID-19 pandemic due to the current limitations in vascular and critical care bed capacity.